2013
DOI: 10.1002/mus.23903
|View full text |Cite
|
Sign up to set email alerts
|

Muscle weakness, fatigue, and torque variability: Effects of age and mobility status

Abstract: Introduction Whereas deficits in muscle function, particularly power production, develop in old age and are risk factors for mobility impairment, a complete understanding of muscle fatigue during dynamic contractions is lacking. We tested hypotheses related to torque-producing capacity, fatigue resistance, and variability of torque production during repeated maximal contractions in healthy older, mobility-impaired older, and young women. Methods Knee extensor fatigue (decline in torque) was measured during 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 37 publications
1
28
0
2
Order By: Relevance
“…The CV was associated with greater fatigability (both peak velocity and torque reductions, with young and old included) and associated with the six-minute walk distance among the old adults. Large age-related variability during a dynamic fatiguing task with the ankle dorsiflexor muscles had been previously observed in mobility-impaired old females compared with age-matched females (not mobility impaired) and healthy young females (Kent-Braun and others 2014). The old adults in the current study were not mobility impaired, but there was a difference between age groups for the knee extensors.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The CV was associated with greater fatigability (both peak velocity and torque reductions, with young and old included) and associated with the six-minute walk distance among the old adults. Large age-related variability during a dynamic fatiguing task with the ankle dorsiflexor muscles had been previously observed in mobility-impaired old females compared with age-matched females (not mobility impaired) and healthy young females (Kent-Braun and others 2014). The old adults in the current study were not mobility impaired, but there was a difference between age groups for the knee extensors.…”
Section: Discussionmentioning
confidence: 70%
“…Fatigue induced by exercise may further exacerbate the age-related increases in variability of a motor task. One study showed that during a dynamic fatiguing task with the knee extensor muscles, old females (65–85 years) with impaired mobility exhibited greater torque variability compared with healthy old (not mobility impaired) and healthy young females (Kent-Braun and others 2014). Less is known about the age-related variability of contraction velocity of upper extremity muscles during a fatiguing task which may potentially impair functional performance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the triceps surae has important functional roles in gait and balance, and has been extensively studied in health and aging, to provide comparative data (Tracy et al 1999;McNeil et al 2005;Kent-Braun et al 2014). Histochemical studies have shown that the TA contains 70-75% type I fibers (Monster et al 1978), and similarly the soleus, is rather homogeneous, being composed of 80% type I muscle fibers (Monster et al 1978;Kent-Braun et al 2014). However, unlike the TA, the soleus muscle has been shown to be spared from age-related muscle atrophy, contractile slowing, and a loss of motor units when compared to the TA (Dalton et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A associação estatística significativa entre a idade e o marcador força de preensão manual, identificada neste estudo e em outras investigações (8)(9) , pode ser explicada pela redução do número e tamanho das fibras musculares, em especial as fibras do tipo II (contração rápida), responsáveis pela produção de força muscular (22) . Nos longevos, a prevalência de perda de massa e força muscular é alta e pode comprometer indicadores importantes como a velocidade da marcha, força de preensão manual e a energia (23) .…”
Section: Discussionunclassified